Sistem Pendukung Keputusan Diskon Asuransi Dengan Metode Smarter - Wirawan Galeh Pradhana; Albert Yakobus Chandra (Prodi Sistem Informasi Universitas Dharma Andalas, 2021)
In the midst of fierce competition in the market share of car body repair and paint services with independent workshops in Yogyakarta, Nasmoco Bantul is expected to attract as many customers as possible to be able to carry out body and paint repairs, especially customers who use insurance whose percentage reaches 70% (based on the average monthly invoice data of Nasmoco Bantul). However, this has not reached the expected target because Nasmoco Bantul does not yet have a database that stores customer data complete with the insurance used. So in the research, a database system will be created that will manage and store customer data along with the insurance they use which later information from the database can be used to carry out the marketing process for body paint repairs. And this system is also equipped with an decision support system which aims to assist management in determining the provision of discounts to insurance company partners by using several indicators. This system is a web-based application that uses the CodeIgniter framework. The decision support system method used in determining discounting uses the SMARTER method.